2022
DOI: 10.1177/00315125221139000
|View full text |Cite
|
Sign up to set email alerts
|

Age and Gender Differences in Achievement Goal Orientations in Relation to Physical Activity

Abstract: Our aim in the study was to examine age and gender differences in achievement goal orientations and their impact on self-reported persistence toward physical activities of middle school, high school, and college students. A total of 1254 students from four middle schools, two high schools, and one university participated in this study. Multiple regression analyses revealed that age, as a continuous variable, had a significant and positive effect on students’ mastery-approach goals, performance-approach goals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…This study showed grade differences in performanceavoidance goal orientation (e.g., performance-approach of junior high school students was significantly lower than that of senior high school students, but performance-avoidance and learning anxiety of junior high school students were significantly higher than that of senior high school students), which is partially consonant with some studies (Meece et al, 2006a;Guan et al, 2023) and inconsonant with others (Cecchini-Estrada et al, 2011;Guan et al, 2020). Guan et al (2023) revealed that age, as a continuous variable, had a significant and positive effect on students' mastery-approach goals, performance-approach goals, and mastery-avoidance goals, and a negative effect on students' performance-avoidance goals. However, we only found performance-avoidance goals were negatively related to students' age and performance-approach goals were positively related to students' age.…”
Section: Characteristics Of Achievement Goal Approach Peer Interactio...supporting
confidence: 87%
See 4 more Smart Citations
“…This study showed grade differences in performanceavoidance goal orientation (e.g., performance-approach of junior high school students was significantly lower than that of senior high school students, but performance-avoidance and learning anxiety of junior high school students were significantly higher than that of senior high school students), which is partially consonant with some studies (Meece et al, 2006a;Guan et al, 2023) and inconsonant with others (Cecchini-Estrada et al, 2011;Guan et al, 2020). Guan et al (2023) revealed that age, as a continuous variable, had a significant and positive effect on students' mastery-approach goals, performance-approach goals, and mastery-avoidance goals, and a negative effect on students' performance-avoidance goals. However, we only found performance-avoidance goals were negatively related to students' age and performance-approach goals were positively related to students' age.…”
Section: Characteristics Of Achievement Goal Approach Peer Interactio...supporting
confidence: 87%
“…In this study, we found significant gender differences for masteryavoidance goal orientation, peer interaction, and learning anxiety (i.e., girls had slightly stronger mastery-avoidance goals, learning anxiety, and intimate relationships in peer interactions than their male counterparts, and lower social anxiety and common activity in peer interactions). Achievement goal results were partially consistent with some studies (Cecchini-Estrada et al, 2011;Lochbaum et al, 2019) and partially inconsistent with other previous findings (Meece et al, 2006b;Bahar et al, 2018;Guan et al, 2023;Hemi et al, 2023). Gender differences in learning anxiety were consistent with some previous research (Hill and Sarason, 1975;Maccoby and Jacklin, 1998;Ho et al, 2000), whereas other studies indicated there were no or fewer gender differences (Elsequest et al, 2010;Olmez and Ozel, 2012;Goetz et al, 2013).…”
Section: Characteristics Of Achievement Goal Approach Peer Interactio...supporting
confidence: 64%
See 3 more Smart Citations